Peningkatan Kemampuan Guru-Guru Kelompok Kerja Madrasah (KKM) MA Ma’arif 03 Kabupaten Demak untuk Sertifikasi Microsoft Office Specialist Powerpoint - Aria Hendrawan; Agusta Praba Ristadi Pinem; Soiful Hadi (Jurnal Surya Masyarakat, 2022)
Microsoft Office functions are very important to support various work related to offices and multimedia.  In today's era, almost all office work requires Microsoft Office programs in its completion, not to mention in the world of education.  Microsoft Office itself is a collection of software applications that are used to process, store, and combine data in the form of documents. One of the Microsoft Office Specialist (MOS) programs is PowerPoint, where the PowerPoint features really is supports the process of implementing education, especially for teachers who is teaching students.  With the recognition of MOS, teachers will have the ability to take advantage of features, especially features in PowerPoint that can be implemented in the teaching and learning process.  Awareness of MA Ma'arif's 03 KKM (Kelompok Kerja Madrasah) teachers in Kab.  Demak for the development of information technology to be creative and innovative in creating interesting teaching media for students is the background for this service activities.  This activities are carried out using the method of direct mentoring to partners through MOS PowerPoint training and exams. The results of the MOS PowerPoint training evaluation, 100% of participants passed the exam. the implementation of community service has succeeded in achieving the goals and targets that have been set, seen from the positive responses from participants whose all assistance is training and is relevant to needs.